MEMBONGKAR MITOS KECANTIKAN DAN BUDAYA KONSUMEN DALAM CHICK LIT ‘BEAUTY CASE’ KARYA ICHA RAHMANTI - Tania Intan; Prima Agustina Mariamurti (Universitas Negeri Malang, 2019)
This study aims to dismantle the myths of beauty and consumer culture in the second chick lit of Icha Rahmanti, entitled Beauty Case (2005). The novel was examined using a feminist literary criticism approach and analyzed using descriptive-qualitative methods. The theoretical references used mainly are the ideas of Wolf (2017) to interpret beauty in various contexts, as well as the meaning of beauty in colonial and market discourse according to Priyatna (2018b). The issue of consumer culture is further discussed with the rationale of Wilson (1985) and Bowlby (1993). The results showed that: (1) in accordance with Wolf's ideas, the forms of beauty myths revealed in the novel included moving in the areas of work, culture, and sexuality. (2) The consumer culture that is experienced by the main characters and other female characters in the novel is the impact of the beauty myth, namely because of the desire to be seen, the demands of the environment, and the desire to look young.Penelitian ini bertujuan untuk membongkar mitos kecantikan dan budaya konsumen dalam chick lit Beauty Case (2005), karya kedua dari Icha Rahmanti. Novel tersebut dikaji dengan pendekatan kritik sastra feminis dan dianalisis dengan metode deskriptif-kualitatif. Referensi teoritis yang digunakan terutama adalah gagasan Wolf (2017) untuk menafsir kecantikan dalam berbagai konteks, serta makna kecantikan dalam wacana kolonial dan pasar menurut Priyatna (2018b). Isu budaya konsumen selanjutnya dibahas dengan landasan pemikiran dari Wilson (1985) dan Bowlby (1993). Hasil penelitian menunjukkan bahwa: (1) sesuai dengan gagasan Wolf, bentuk-bentuk mitos kecantikan yang terungkap dalam novel tersebut bergerak dalam wilayah pekerjaan, kultur, dan seksualitas. (2) Budaya konsumen yang dihayati oleh tokoh utama dan tokoh-tokoh perempuan lainnya dalam novel tersebut merupakan dampak dari mitos kecantikan, dan didasari oleh keinginan untuk dipandang, tuntutan dari lingkungan, dan hasrat untuk tampil muda.